Heuristic Strategies of Self-Regulated Learning in University Students. / Estrategias heurísticas para el aprendizaje autorregulado en estudiantes universitarios . - OSEDA GAGO, Dulio; MENDIVEL GERONIMO, Ruth Katherine; FLORES AROCUTIPA, Javier Pedro; LUJAN MINAYA, Julio Cesar (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The research starts from the objective of demonstrating, whether the application of heuristic strategies strengthens self-regulated learning in students of the National University of Cañete. The research belongs to the applied type and explanatory level, with a pre-experimental design, for the sample, 343 students from the Professional School of Systems Engineering were taken probabilistically. The main results show us that self-regulated learning has improved by 16.17%, then in its components learning to learn by 12.19%, in the domain of specific learning by 18.42%, and in the use of computer resources 17.90%. Then, it is concluded with the Wilcoxon test with a p-value: (0.000 <0.050) considers that the application of heuristic strategies has favorably and significantly strengthened the self-regulated learning of the students of the National University of Cañete. RESUMEN El estudio parte del objetivo de demostrar si la aplicación de las estrategias heurísticas fortalece el aprendizaje autorregulado en los estudiantes de la Universidad Nacional de Cañete. La investigación, pertenece al tipo aplicada y nivel explicativo, con diseño pre-experimental; la muestra probabilística se tomó a 343 estudiantes de la Escuela Profesional de Ing. de Sistemas. Los principales resultados dan cuenta que ha mejorado en un 16,17% el aprendizaje autorregulado; luego sus componentes aprender a aprender en un 12,19%, en el dominio de un aprendizaje específico un 18,42%, y en el uso de recursos informáticos un 17,90%. Se concluye con la prueba de Wilcoxon con un valor-p: (0.000<0.050) considerando que la aplicación de las estrategias heurísticas han fortalecido favorable y significativamente el aprendizaje autorregulado de los estudiantes de la Universidad Nacional de Cañete.